CONSUMER RIGHTS PROTECTION IN GROUP ORDER PRACTICES: LEGAL ANALYSIS OF SELLER LIABILITY - Anjani, Diva Rafi; Wulandari, Ayun Novita; Aulia, Alifiana Arif Rahmah (International Peneliti Ekonomi, Sosial dan Teknologi, 2025)
This study analyzes legal protection for consumers and seller liability in the practice of Group Order (GO), a collective ordering mechanism popular in the digital era but often gives rise to problems such as default, delays, non-conforming goods, and fraud. Using normative legal research methods through analysis of the Civil Code, Commercial Code, Consumer Protection Law, and expert doctrines, this study assesses the legal relationship between GO admins, sellers, and consumers as a contractual relationship that gives rise to rights and obligations. Forms of default include non-delivery of goods, goods not as described, or unjustified delays. Both sellers and GO admins can be held accountable and consumers have the right to obtain compensation, refunds, or settlement through the BPSK or litigation channels. This study emphasizes the need for strengthening regulations and supervision so that GO practices are more transparent, accountable, and able to provide legal certainty for consumers.